AKSERELASI PERTUMBUHAN STUMP JATI (Tectona grandis L.f.) DENGAN PEMOTONGAN BATANG DAN INOKULASI MIKORIZA - Efendi Efendi; Syammiah Syammiah; Muhammad Iqbal (Jurnal Floratek, 2012)
A study was carried out to attempt accelerating growth of teak stump by stem cutting and inoculation of Mycorrhiza. Three months-old-seedlings of teak were cut and inoculated with mychorryza. Results of the study showed that growth of teak stump, including stem height, plant height, stem diameter, numbers of leaves, length of leaves, and fresh weight of the teak plant were significantly affected by cutting stem and inoculation of Mycorrhiza. We found that length of stem, length of plant, stem diameter, numbers of leaves, length of leaves were of significantly-positive responses to stem cutting. Additionally, inoculation of Mycorrhiza also successfully accelerated growth of teak stump, including stem, leaves, and biomass. This study found a non-significant interaction between the cutting stem and inoculation of Mycorrhiza. The present study revealed that the cutting stem 2.5-7.5 could be considered as the optimum treatment to enhance growth of teak stump. Moreover, inoculation of Mycorrhiza with 2.5 g/polybag was the optimum dosage to enhance growth of teak stump. The dosage of Mycorrhiza inoculation did not depend on length of cutting stem.